Leaning against the bubble: Central Bank intervention in Walrasian asset markets - Chia-ling Chang; Jukka Ilomäki; Hannu Laurila (Risks, 2021)
The paper presents a two-period Walrasian financial market model composed of informed and uninformed rational investors, and noise traders. The rational investors maximize second period consumption utility from the payoffs of trading risk-free holdings to risky assets in the first period. The central bank reacts directly to asset price movements by selling or buying assets to stabilize the market price. It is found that the intervention makes the risky asset's market price per share less sensitive to information shocks, which presses the market price towards its average price thus reducing price variance. The informed investors' prediction coefficient remains unaffected, but that of the uninformed investors is magnified, which cancels out the negative effect on shock sensitivity thus keeping the expected value of the risky asset's dividend constant. Finally, the introduction of the policy rule does not affect rational investors' risk per share. A general conclusion is that the central bank's policy can be regarded as an effective automatic stabilizer of financial markets
Keywords: 330; asymmetric information; CARA; expectations; Walrasian financial markets